2018
DOI: 10.1007/s10611-017-9766-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulatory investments among private actors in the era of regulatory capitalism: the licensing of Swedish finance and securities industry employees

Abstract: This article analyses the growth of the Swedish finance and securities industry's employee licensing programme to advance our understanding of the growth, conditions, and function of various forms of self-regulation in the era of regulatory capitalism. It examines how the situations that are significant for private actors' initiation and implementation of self-regulation are connected with the development of a particular form of self-regulation. The article argues that the licensing programme in question is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to authors of paper [6], it is clear that the nonextensibility of the share of alternative investments in the institutional investment portfolio may be due to the optimization of historical data. The period of stagnation since the 1990s, and the growth of the securities market, has become somewhat dramatic [7]. Insider trading has been a topic of interest for many researchers and it has been found that insider trading reduces liquidity and increases trading costs [8][9][10][11][12].…”
Section: Methodological Foundationsmentioning
confidence: 99%
“…According to authors of paper [6], it is clear that the nonextensibility of the share of alternative investments in the institutional investment portfolio may be due to the optimization of historical data. The period of stagnation since the 1990s, and the growth of the securities market, has become somewhat dramatic [7]. Insider trading has been a topic of interest for many researchers and it has been found that insider trading reduces liquidity and increases trading costs [8][9][10][11][12].…”
Section: Methodological Foundationsmentioning
confidence: 99%
“…From the regulator's point of view, self-regulation is a way to “adopt policies which improve observable features of the activity and give the appearance of service unity” (Ogus and Carbonara, 2011 , p. 239). The focus is “directed toward promoting transparency and the ability of market participants to make informed choices” (Engdahl, 2018 , p. 580). Unease with the normative asymmetry, regulated industries, on the other hand, view self-regulation as a process that is more within their control to shape the direction of the market and ward off government intervention (Norman, 2011 ).…”
Section: Self-regulation In Financementioning
confidence: 99%
“…Unease with the normative asymmetry, regulated industries, on the other hand, view self-regulation as a process that is more within their control to shape the direction of the market and ward off government intervention (Norman, 2011 ). Self-regulation influences information flow and oversees the marketplace to ensure fair and transparent transactions (Christmann and Taylor, 2006 ; Heath, 2006 ; Engdahl, 2018 ).…”
Section: Self-regulation In Financementioning
confidence: 99%
See 2 more Smart Citations